Modelos de concess\~ao de rodovias no Brasil, no México, no Chile, na Colômbia e nos Estados Unidos: Evoluç\~ao histórica e avanços regulatórios - Carlos Álvares da Silva Campos Neto; Sérvulo Vicente Moreira; Lucas Varj\~ao Motta (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The adequate availability of infrastructure and its related services, is mandatory condition for further development of the country's competitive advantages, intensifying the productive specialization. Due to limited financial capacity, in the course of the last three decades, there have been an increasing private participation in these sectors under privatizations, concessions and Private-Public Partnerships (PPPs). This work has the following goals: i) to summarize the evolution of the concession's system in Brazil, Mexico, Chile, Colombia and USA, aiming to identify the characteristics and alternatives developed by each country; and ii) to conduct an economic analyze of the concession contracts between the public and private entities, focusing on the economic regulation aspects. We found a learning historic evolution, based in continuous enhancement of the public policy and in different degrees of success. The economic regulation aims to evolve in several issues as the risk-sharing, application of incentives and penalization and selection criteria, in despite of the difficulties created by economic crises. It's worth highlighting some innovations as: (Brazil) use of an "Investment trigger" to require capacity expansion; Use of real demand to reset the Financial-Economic Equilibrium (EEF); Distribution of productivity gains (Factor X); Use of the concession length as a tool to reset the EEF; (Chile) MVPR as selection criteria and risk-sharing tool; MCC as exchange rate risk-sharing tool; (Mexico) use of an account to accommodate the facility return at the concession end; Penalties grading system; (Colombia) use of a Trust Fund; Minimum revenue guarantee mechanism (MGR); (USA) Legislation and financial innovations; DBFOM mechanism. Part of the foreigner experience may contribute for the improvement of the Brazilian concession model. Notoriously, learning from the Mexican and Colombian experience, there are some policies shouldn't be carried out in Brazil. From the Chilean, the MVPR stands out as a solid success, commonly replicated by other countries. It's worth noting that Brazil has the largest share of highways under concession. Furthermore, it's possible that the share is near to its own limit (around 25%), as the highways that can attract the private sector, based on the vehicle flow, are mostly already contracted. To the left part of the share there are two alternatives: sponsored PPP and/or public resources. The PPPs mechanism, which includes fee payment from the private investor and requires the highway availability, would involve a cross-subsidy between the financially viable and non-viable projects using a trust fund. This mechanism failed in Chile. Beyond that, it's worth noting that the use of cross-subsidy creates unwelcome economic signs and, since Adam Smith, it's well known that it doesn't stimulates good results. The majority of the highway network is not attractive for private investor, thanks to low intensity traffic, requiring the use of public resources.
Keywords: L51; L92; R48; 330; highway concessions; economic regulation; concession's agreement; public-private partnership